The Impact of Artificial Intelligence on Financial Ratios Indicating Financial Distress: Evidence from NYSE-Listed Companies - Sana Ramzan (International Journal of Management and Data Analytics, 2025)
This study investigates the impact of artificial intelligence (AI) adoption on key financial ratios indicative of financial distress among 2000 companies listed on the New York Stock Exchange (NYSE) for 2022 and 2023. Using a quantitative methodology, AI adoption and financial ratios like the Debt-to-Equity Ratio, Current Ratio, and Return on Assets (ROA) are examined using regression and correlation analysis to determine how AI affects corporate financial health. The findings reveal that AI adoption is associated with a significant reduction in the Debt-to-Equity Ratio, improved liquidity through a higher Current Ratio, and increased profitability through ROA. These findings suggest that AI-adopting organizations may better manage financial leverage, liquidity, and asset utilization. The research contributes to the literature on AI's role in financial performance and informs investors, creditors, and regulators about AI's strategic advantages in mitigating financial distress.